Measuring heterogeneity in perceived satisfaction of private vehicle users towards attributes affecting access to metro stations: A case study of Delhi. Issue 3 (September 2022) - Kar, Manaswinee; Sadhukhan, Shubhajit; Parida, Manoranjan
Highlights: Heterogeneity in perceived satisfaction with metro station access is investigated. Nonparametric tests capture perceptional heterogeneity across various user groups. Gender and Age-group have significant influences on users' perceived satisfaction. RIDIT analysis obtains derived rankings of attributes for varied user groups. Users are highly satisfied with Egress time and dissatisfied with Presence of VMS. Abstract: The present study measures the heterogeneity in perceived satisfaction of private vehicle users (use private cars and motorised two-wheelers) based on 'gender' and 'age-group' towards 17 selected attributes influencing access to metro stations in Delhi, India. A tablet-based survey instrument was designed to collect satisfaction related responses of private vehicle users on a 6-point Likert-type ordinal scale along with their socioeconomic and travel information. Mann-Whitney U and Wilcoxon W tests were performed on the database to capture perceptional heterogeneity across various user groups classified based on 'gender' and 'age-group' towards satisfaction of the attributes influencing access. The Relative to an Identified Distribution Integral Transformation (RIDIT) analysis was employed to obtain derived satisfaction rankings of attributes from the perspective of the aforementioned user groups. The outcomes of the study indicate the presence of heterogeneity in perceived satisfaction and rankings of attributes between 'male-female' and '<30 years and ≥30 years age-group' respondents. The study findings will help transport planners and policymakers in improving access to the metro stations, considering the requirements of different user groups.